Opioid-free anaesthesia reduces postoperative nausea and vomiting after thoracoscopic lung resection: a randomised controlled trial - Feng, Chang-dong; Xu, Yu; Chen, Shaomu; Song, Nan; Meng, Xiao-wen; Liu, Hong; Ji, Fu-hai; Peng, Ke (British journal of anaesthesia : BJA, 2024)
Intraoperative opioid use has a positive relationship with postoperative nausea and vomiting (PONV), and opioid-free anaesthesia (OFA) might reduce PONV. We investigated whether OFA compared with opioid-based anaesthesia would reduce PONV during the first 2 postoperative days among patients undergoing thoracoscopic lung resection. In this randomised controlled trial, 120 adult patients were randomly assigned (1:1, stratified by sex) to receive either OFA with esketamine, dexmedetomidine, and sevoflurane, or opioid-based anaesthesia with sufentanil and sevoflurane. A surgical pleth index (SPI) of 20-50 was applied for intraoperative analgesia provision. All subjects received PONV prophylaxis (dexamethasone and ondansetron) and multimodal analgesia (flurbiprofen axetil, ropivacaine wound infiltration, and patient-controlled sufentanil). The primary outcome was the occurrence of PONV during the first 48 h after surgery. The median age was 53 yr and 66.7% were female. Compared with opioid-based anaesthesia, OFA significantly reduced the incidence of PONV (15% vs 31.7%; odds ratio [OR]=0.38, 95% confidence interval [CI], 0.16-0.91; number needed to treat, 6; P=0.031). Secondary and safety outcomes were comparable between groups, except that OFA led to a lower rate of vomiting (OR=0.23, 95% CI, 0.08-0.77) and a longer length of PACU stay (median difference=15.5 min, 95% CI, 10-20 min). The effects of OFA on PONV did not differ in the prespecified subgroups of sex, smoking status, and PONV risk scores. In the context of PONV prophylaxis and multimodal analgesia, SPI-guided opioid-free anaesthesia halved the incidence of PONV after thoracoscopic lung resection, although it was associated with a longer stay in the PACU. Chinese Clinical Trial Registry (ChiCTR2200059710).